2008
DOI: 10.1504/ijamechs.2008.020839
|View full text |Cite
|
Sign up to set email alerts
|

A ZigBee-based mobile tracking system through wireless sensor networks

Abstract: Wireless sensor networks have been deployed widely. Sensor networks involve sensor nodes which are very small in size, low in cost and have a short battery-life. One of the critical wireless sensor network applications is localisation and tracking mobile sensor nodes. ZigBee is a new emerging technology for low rate, low power and low range communication networks, which aims to provide long battery life for network devices. In this paper, we discuss various localisation and tracking techniques and categorise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…The results from [2] showed that the weighted RSSI-values give a more accurate position than the normal RSSI-values. For Several tests have been executed.…”
Section: A Range-based: Weightedmentioning
confidence: 98%
See 3 more Smart Citations
“…The results from [2] showed that the weighted RSSI-values give a more accurate position than the normal RSSI-values. For Several tests have been executed.…”
Section: A Range-based: Weightedmentioning
confidence: 98%
“…The first one is a range-based solution described by Tareq Ali Alhmiedat et al in [2]. The proposed algorithm is based on weighted RSSI values.…”
Section: A Range-based: Weightedmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, an RSS-based mobile tracking approach usually consists of a set of static nodes with known location information, referred to as reference nodes. The tracking algorithm tries to continuously estimate the mobile target's location from the RSS measurements between the mobile target and its neighboring reference nodes [3], [4]. Since existence of multipath fading, reflections, diffraction and interference highly affects the correspondence between the RSS and relative distance, more works [5], [6] are proposed to minimize the dynamic fluctuation of the radio signal received from each reference node.…”
Section: Introductionmentioning
confidence: 99%